FENOMENA SOCIAL LOAFING PADA MAHASISWA DALAM PENGERJAAN TUGAS KELOMPOK: STRATEGI, KETERGANTUNGAN, DAN DIFUSI TANGGUNG JAWAB - Erna Puji Lestari; Riskiyana Prihatiningsih; Ella Faridati Zen (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to reveal the dynamics of student behavior in the context of working on group assignments in the lecture environment. Through a qualitative approach, various patterns of student participation were found that reflected adaptation strategies to collective responsibility, procrastination tendencies, and social dependence. Data was collected through in-depth interviews and participatory observation of student group activities in completing academic assignments. The results of the study showed that students tended to choose easy tasks, postpone work until they were close to the deadline, avoid leadership positions, and adjust the intensity of contributions based on the quality of group members. This phenomenon indicates the diffusion of social responsibility and efficiency strategies in the context of collaborative learning. This research provides implications for lecturers to design an assessment system and evaluation mechanism that fosters a sense of personal responsibility in group work. Keyword: Group Assignments, Student Participation, Procrastination, Social Dependence, Collective Responsibility Abstrak: Penelitian ini bertujuan untuk mengungkap dinamika perilaku mahasiswa dalam konteks pengerjaan tugas kelompok di lingkungan perkuliahan. Melalui pendekatan kualitatif, ditemukan berbagai pola partisipasi mahasiswa yang mencerminkan strategi adaptasi terhadap tanggung jawab kolektif, kecenderungan prokrastinasi, serta ketergantungan sosial. Data dikumpulkan melalui wawancara mendalam dan observasi partisipatif terhadap aktivitas kelompok mahasiswa dalam menyelesaikan tugas akademik. Hasil penelitian menunjukkan bahwa mahasiswa cenderung memilih tugas yang mudah, menunda pengerjaan hingga mendekati batas waktu, menghindari posisi kepemimpinan, serta menyesuaikan intensitas kontribusi berdasarkan kualitas anggota kelompok. Fenomena ini mengindikasikan adanya difusi tanggung jawab dan strategi efisiensi sosial dalam konteks pembelajaran kolaboratif. Penelitian ini memberikan implikasi bagi dosen untuk merancang sistem penilaian dan mekanisme evaluasi yang menumbuhkan rasa tanggung jawab personal dalam kerja kelompok. Kata kunci: Tugas Kelompok, Partisipasi Mahasiswa, Prokrastinasi, Ketergantungan Sosial, Tanggung Jawab Kolektif